2014
DOI: 10.22495/cocv11i3conf2p6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the financial crisis on risk disclosures: a comparative study of U.S. and Canadian corporations

Abstract: The effect of the financial crisis on enterprise risk management (ERM) disclosures was examined through a content analysis of the 2007 and 2008 annual reports of S&P 500 and S&P- TSX Composite companies in the energy, materials, industrials, and consumer discretionary sectors. Fourteen types of risk were tracked and categorized. The total number of risk disclosures by S&P 500 companies hardly increased at all from 2007 to 2008, while the total number of risk disclosures by TSX companies increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Our finding are not consistent with the findings of Maingot et al [10]- [12] who reported very few changes in the assessment of risk exposure, consequences and ERM strategies in the Canadian financial and non-financial corporations and in the US non-financial corporations. While these research studies reflect the poor communication strategies concerning ERM for their particular samples, our findings show significant changes in the as-sessment of ERM after the crisis, and this may reflect the efficiency and the credibility of the ERM disclosure strategies utilized by the largest US banks.…”
Section: Analysis Of the Results And Conclusioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our finding are not consistent with the findings of Maingot et al [10]- [12] who reported very few changes in the assessment of risk exposure, consequences and ERM strategies in the Canadian financial and non-financial corporations and in the US non-financial corporations. While these research studies reflect the poor communication strategies concerning ERM for their particular samples, our findings show significant changes in the as-sessment of ERM after the crisis, and this may reflect the efficiency and the credibility of the ERM disclosure strategies utilized by the largest US banks.…”
Section: Analysis Of the Results And Conclusioncontrasting
confidence: 99%
“…3) List of risks and categories in the banking sector After examining ERM information disclosed in the annual reports of the US largest banks through the 4 year period of investigation, we identified a list of 15 types of banking risks and classified them according to three categories [12]- [35]:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations